Innovation on Media Audiovisual IT- Based For Learning Arabic Language in SMK PPTQ MBS Daarun Najah Klaten - Regita, Rahma; Inayati, Nurul Latifatul; Tamami, Fauziyah Qurrota A’yun (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2024)
This study describes the use of audio-visual technology as a medium for learning Arabic to improve listening skills for students. The problem of education and teaching is a fairly complex one where many factors influence it. One of these factors is the teacher. The success of teachers in delivering material depends on the smooth interaction between teachers and their students. The purpose of this study is to develop Arabic language learning using IT-based media by watching and listening to improve listening skills for students. The use of this learning medium has an influence on learning Arabic at SMK PPTQ MBS Daarun Najah Klaten based on audiovisuals, namely by increasing motivational learning, improving listening skills, increasing vocabulary mastery, improving speaking skills, making them easily accessible, and increasing creativity. Although learning media has its influence and advantages, it also has disadvantages that must be anticipated. The most prominent influence is in terms of shortcomings. The presence of audio-visual content has a negative impact that is not valuable to students; therefore, teachers must be facilitators who are engaged in filtering content so that teaching materials in the media are in accordance with learning objectives. Teachers also have an important role in fostering student learning motivation with various types of audio-visual learning; this is an obligation that must be carried out by teachers considering the optimization of the use of audio-visual-based learning media that use this information technology (IT). In its implementation, students must be able to develop their abilities independently after participating in information technology (IT)-based learning provided by the teacher. In this case, evaluation is also needed as an indication of student understanding. Evaluation can be in the form of written and oral tests.